Side-channel analysis of SEcube™ platform - Bollo, Matteo; Carelli, Alberto; Di Carlo, Stefano; Prinetto, Paolo (East-West Design and Test Symposium, 2017)
Cryptography provides techniques to cypher and de-cypher sensitive information through a token called key in order to store and transmit it across insecure networks. The goal of cryptography is to protect information from potential attackers and to enable access to authorized users only. Several hardware cryptographic devices are entering the market. However, these devices can be subject to passive attacks that consist in retrieving secret data by observing the side-channel behaviour of the device (i.e. execution time, power consumption, electromagnetic field). This work studies the robustness of SEcube™, an innovative secure hardware product against Differential Power Analysis attacks. SEcube™ is a system-on-chip equipped with three devices interconnected and embedded in a single chip: an ARM Cortex M4 low-power processor, a Lattice MachXO2-7000 FPGA and a SmartCard SLJ52G (EAL5+ certified). Moreover, in order to examine the security enhancement of this platform, we perform the same analysis with a similar board equipped with the same microprocessor and then compare the results. Experimental results show that the number of correct bits is similar between the two platform.